Postnatal Environmental Tobacco Smoke Exposure Related to Behavioral Problems in Children - Chastang, Julie; Baïz, Nour; Cadwalladder, Jean Sébastien; Robert, Sarah; Dywer, John; Charpin, Denis André; Caillaud, Denis; de Blay, Frédéric; Raherison, Chantal; Lavaud, François; Annesi-Maesano, Isabella (PloS one, 2015)
The purpose of this study was to examine the association between pre and post environmental tobacco smoke (ETS) exposure and behavioral problems in schoolchildren. In the cross-sectional 6 cities Study conducted in France, 5221 primary school children were investigated. Pre- and postnatal exposure to secondhand tobacco smoke at home was assessed using a parent questionnaire. Child's behavioral outcomes (emotional symptoms and conduct problems) were evaluated by the Strengths and Difficulties Questionnaire (SDQ) completed by the parents. ETS exposure during the postnatal period and during both pre- and postnatal periods was associated with behavioral problems in children. Abnormal emotional symptoms (internalizing problems) were related to ETS exposure in children who were exposed during the pre- and postnatal periods with an OR of 1.72 (95% Confidence Interval (CI)= 1.36-2.17), whereas the OR was estimated to be 1.38 (95% CI= 1.12-1.69) in the case of postnatal exposure only. Abnormal conduct problems (externalizing problems) were related to ETS exposure in children who were exposed during the pre- and postnatal periods with an OR of 1.94 (95% CI= 1.51-2.50), whereas the OR was estimated to be 1.47 (95% CI=1.17-1.84) in the case of postnatal exposure only. Effect estimates were adjusted for gender, study center, ethnic origin, child age, low parental education, current physician diagnosed asthma, siblings, preterm birth and single parenthood. Postnatal ETS exposure, alone or in association with prenatal exposure, increases the risk of behavioral problems in school-age children.